Targeting molecular pathways to control immune checkpoint inhibitor toxicities - Reschke, Robin Niklas; Sullivan, Ryan J.; Lipson, Evan J.; Enk, Alexander; Gajewski, Thomas F.; Hassel, Jessica C. (Trends in immunology, 2024)
Immune checkpoint inhibitors (ICIs) have transformed cancer treatment but are frequently associated with immune-related adverse events (irAEs). This article offers a novel synthesis of findings from both preclinical and clinical studies, focusing on the molecular mechanisms driving irAEs across diverse organ systems. It examines key immune cells, such as T cell subsets and myeloid cells, which are instrumental in irAE pathogenesis, alongside an in-depth analysis of cytokine signaling [interleukin (IL)-6, IL-17, IL-4), interferon γ (IFN-γ), IL-1β, tumor necrosis factor α (TNF-α)], integrin-mediated interactions [integrin subunits αITGA)4 and ITGB7], and microbiome-related factors that contribute to irAE pathology. This exploration of modifiable pathways uncovers new opportunities to mitigate irAEs by using available antibodies (Abs) that target key inflammatory molecules across tumor types, while ideally preserving the antitumor efficacy of ICIs.